Pisciculture : a growth industry? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Pisciculture : a growth industry?Pisciculture has not been developed in any major way in Africa. A few ponds have been constructed in some savannah lands, cages have been set up in rivers, enclosures have been built to try and exploit the potential...